1989
DOI: 10.1002/etc.5620081207
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of nitrogen, oxygen and sulfur heterocyclic compounds under anaerobic conditions: Studies with aquifer samples

Abstract: The potential for anaerobic biodegradation of 12 heterocyclic model compounds was studied. Nine of the model compounds were biotransformed in aquifer slurries under sulfate‐reducing or methanogenic conditions. The nitrogen and oxygen heterocyclic compounds were more susceptible to anaerobic biodegradation than those compounds containing a sulfur heteroatom. Carboxy‐substituted compounds were anaerobically metabolized more readily than unsubstituted or methylated analogues. In methanogenic incubations, 47 to 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 45 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Such knowledge is crucial for conducting metabolic fate studies without predisposing the experiments to failure [29]. In the environment, the release of organosulfur compounds could potentially affect groundwater reserves if they are transported to the terrestrial subsurface [15]. However, organosulfur compounds are typically found only in small amounts in the complex mixtures that make up petroleum, coal, and creosote.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such knowledge is crucial for conducting metabolic fate studies without predisposing the experiments to failure [29]. In the environment, the release of organosulfur compounds could potentially affect groundwater reserves if they are transported to the terrestrial subsurface [15]. However, organosulfur compounds are typically found only in small amounts in the complex mixtures that make up petroleum, coal, and creosote.…”
Section: Discussionmentioning
confidence: 99%
“…All of these compounds have been detected in petroleum [1,3,14]. In addition, some have also been detected in polluted groundwaters [15], and some are accumulated by algae, mosquitoes, and snails [16]. We evaluated these compounds as chemically related groups to assess their impact as mixtures, because that is how they are usually found naturally.…”
Section: Introductionmentioning
confidence: 99%
“…Azaarenes (i.e., PACs in which one carbon atom has been replaced by a nitrogen atom) are present in the environment in amounts up to 1 to 10% of those of their homocyclic analogues [2]. Apart from their natural origin-for example, as alkaloids [3]-and the usual sources of PACs, basic azaarene structures occur as moieties of pharmaceuticals [4,5] and pesticides [6,7]. Special attention will be paid to isomerism, because it has been demonstrated that such slight differences in chemical structure can result in substantial differences in toxicity [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In these chemicals, one or more carbon atoms are substituted with nitrogen, sulfur, or oxygen heteroatoms. This substitution makes NSO‐HETs more water‐soluble and thus mobile compared with their homocyclic analogues (Blotevogel et al ), resulting in long plumes of contamination in groundwater at contaminated sites (Zamfirescu and Grathwohl ) and a substantial risk of contaminating drinking water resources (Kuhn and Suflita ; Meyer ). Particularly high concentrations are found at sites contaminated with tar oil (Brack and Schirmer ; Rasmussen and Olsena ; Tiehm et al ; Blum et al ), a complex mixture of roughly 10 000 chemicals (Collin and Höke ), approximately 85% of which are PAHs and 5 to 13% NSO‐HETs (Meyer ).…”
Section: Introductionmentioning
confidence: 99%